2008
DOI: 10.1248/bpb.31.348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psychotropic Drugs on the 21-Hydroxylation of Neurosteroids, Progesterone and Allopregnanolone, Catalyzed by Rat CYP2D4 and Human CYP2D6 in the Brain

Abstract: Progesterone (PROG) not only is one of the female steroid hormones secreted from the placenta and corpus luteum but also has various functions in the central nervous system as a neurosteroid in the brain.1,2) PROG has the ability to increase myelin-specific protein levels and to enhance the g-aminobutyric acid (GABA)-induced chloride current, 2,3) and the PROG metabolites, 3a-hydroxy-5a-pregnan-20-one (allopregnanolone, ALLO) and 3a,5a-tetrahydrodeoxycorticosterone, act as positive allosteric modulators of GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Values are means of duplicate or triplicate determinations. In addition, we previously reported that psychotropic drugs, such as imipramine, desipramine, and fluoxetine, inhibited 21-hydroxylation of progesterone and allopregnanolone (a neuroactive steroid) mediated by CYP2D6 and CYP2D4 (39). In the present study, we found that imipramine and desipramine, which are tricyclic antidepressants (22)(23)(24), competitively or noncompetitively inhibited dopamine formation from p-tyramine.…”
Section: Imipraminesupporting
confidence: 54%
“…Values are means of duplicate or triplicate determinations. In addition, we previously reported that psychotropic drugs, such as imipramine, desipramine, and fluoxetine, inhibited 21-hydroxylation of progesterone and allopregnanolone (a neuroactive steroid) mediated by CYP2D6 and CYP2D4 (39). In the present study, we found that imipramine and desipramine, which are tricyclic antidepressants (22)(23)(24), competitively or noncompetitively inhibited dopamine formation from p-tyramine.…”
Section: Imipraminesupporting
confidence: 54%
“…The K i values of CBD were 1.16 to 2.69 M, indicating that the inhibitory effect of CBD on CYP2D6 activity is much stronger than that of progesterone. Compared with typical CYP2D6 inhibitors, the inhibitory effect of CBD on recombinant CYP2D6-mediated activity is comparable to those of (S)-nolfluoxetine (K i ϭ 0.84 M), (S)-fluoxetine (K i ϭ 1.27 M) (Shen et al, 2007), desipramine (K i ϭ 1.0 M), and imipramine (K i ϭ 1.4 M) (Niwa et al, 2008). The inhibitory effect of CBD on HLM-mediated CYP2D6 activity is as potent as those of (S,R)-fluoxetine (K i ϭ 1.6 M), desipramine (K i ϭ 1.7 M) (Ball et al, 1997), and 3,4-methylenedioxyamphetamine (K i ϭ 1.8 M) (Wu et al, 1997).…”
Section: Discussionmentioning
confidence: 88%
“…The causes for this could be as follows: 1) Fluox inhibits the cytochrome P450 (CYP) 2D4-mediated 21-hydroxylation of AP, which is one of the main elimination pathways of AP in the brain. 14) Therefore, it is inferred that not only the enhanced AP synthesis, but also the decreased AP metabolic elimination by Fluox dramatically elevated the brain AP level. 2) It has been reported that in the brain, the 17b-hydroxysteroid oxidative activity is higher than the 17-ketosteroid reductive activity for various steroids.…”
Section: Resultsmentioning
confidence: 99%